2018
DOI: 10.1007/s11368-018-2142-9
|View full text |Cite
|
Sign up to set email alerts
|

Early colonization of constructed Technosols by macro-invertebrates

Abstract: Purpose Anthropogenic activities lead to soil degradation and loss of biodiversity, but also contribute to the creation of novel ecosystems. Pedological engineering aims at constructing Technosols with wastes and by-products to reclaim derelict sites and to restore physico-chemical functions. Materials and methods The biological (dynamics of soil and epigeic macroinvertebrate assemblages) and physical (chemical and physical fertility) properties have been studied in two constructed Technosols under grassland d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
(39 reference statements)
0
9
1
Order By: Relevance
“…The macrofauna density in constructed Technosols was in the same range to less disturbed meadows in the North West region of France(Hedde et al, 2019). The diversity was similar to constructed soils with non-hazardous construction and demolition wastes (11.6 ± 4 family groups,Vincent et al, 2018) Hedde et al (2019). andMathieu et al (2005) found similar rapid colonization of respectively a constructed Technosols in a rural landscape of France and of deforested plots by soil macrofauna in Amazonia respectively.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…The macrofauna density in constructed Technosols was in the same range to less disturbed meadows in the North West region of France(Hedde et al, 2019). The diversity was similar to constructed soils with non-hazardous construction and demolition wastes (11.6 ± 4 family groups,Vincent et al, 2018) Hedde et al (2019). andMathieu et al (2005) found similar rapid colonization of respectively a constructed Technosols in a rural landscape of France and of deforested plots by soil macrofauna in Amazonia respectively.…”
mentioning
confidence: 57%
“…neighbouring woods and meadows. The macrofauna density in constructed Technosols was in the same range to less disturbed meadows in the North West region of France(Hedde et al, 2019). The diversity was similar to constructed soils with non-hazardous construction and demolition wastes (11.6 ± 4 family groups,Vincent et al, 2018) Hedde et al (2019).…”
mentioning
confidence: 72%
“…Studies conducted on the nematode community (Villenave et al, 2018) have shown the rapid colonization of Technosols, with a succession of nematode communities established during the study. In other studies, macroinvertebrates, which were absent at the beginning of monitoring, rapidly colonized the Technosols after construction (Hedde et al, 2018).…”
Section: Introductionmentioning
confidence: 71%
“…12 Colonization of an ecological system is a process influenced by a variety of abiotic and biotic factors, but also depends on interspecific interactions and stochastic effects (Melbourne and Hastings, 2009;Clobert et al, 2012). This results in community assemblage dynamics that shift from random associations to interspecific interactions, ultimately reaching a steady state or a dynamic equilibrium within the community (Hedde et al, 2018). Our analysis of the microarthropod community (Fig.…”
Section: Taxonomic Composition Of the Technosol Collembola Communitymentioning
confidence: 98%
See 1 more Smart Citation